The Role Of Computer Technologies In Knowledge Acquisition - Nemani, Rao R. (Journal of Knowledge Management Practice, 2010)
The concept of knowledge management is becoming increasingly interested to both academia and practitioners. The aim of the research is to answer a question ‘the role of computer technologies in knowledge acquisition?’A comprehensive review of literature covering the topics of knowledge management and the organizational knowledge was conducted to answer this question. This literature review seeks to establish the nexus between computer technologies and knowledge management. To achieve this, thorough reviews of articles are done in a number of areas and a significant body of literature on knowledge management is summarized. Based on the review of the literature it has shown that there is a connection between the computer technologies and their role in knowledge acquisition in an organizational setting.